New Frontiers : Law and Society in the Roman World. - Plessis, Paul J. du (Edinburgh University Press, 2013)
An interdisciplinary, edited collection on social science methodologies for approaching Roman legal sources. Roman law as a field of study is rapidly evolving to reflect new perspectives and approaches in research. Scholars who work on the subject are increasingly being asked to conduct research in an interdisciplinary manner whereby Roman law is not merely seen as a set of abstract concepts devoid of any background, but as a body of law which operated in a specific social, economic and cultural context. This "context-based" approach to the study of Roman law is an exciting new field which legal historians must address. Since the mid-1960s, a new academic movement has advocated a "law and society" approach to the study of Roman law instead of the prevailing dogmatic methodology employed in many Faculties of law. This book aims to further the current debate on the interface between legal history and ancient history.It brings together a distinguished group of scholars who will provide different perspectives on this debate. It addresses particular themes within this debate such as law and legal practice, law and gender as well as law and economics.